Celiac disease may be rare among children in South China. Issue 2 (February 2022) - Liang, Cui-ping; Geng, Lan-Lan; Chen, Pei-Yu; Li, Hui-Wen; Ren, Lu; Gong, Si-Tang
Objective: The prevalence of celiac disease (CD) varies geographically and ethnically; however, the prevalence among children in South China remains unknown. We therefore determined the occurrence of CD among Chinese children in South China. Methods: Serum samples were collected from children and assessed for anti-tissue transglutaminase IgA antibodies (anti-tTG-IgA) and total IgA. Anti-tTG-IgA+ participants underwent human leukocyte antigen (HLA) DQ2/DQ8 determination. Samples with serum total IgA <0.05 g/L were also analyzed for anti-tTG-IgG, and for HLA-DQ2/DQ8 if the values were above borderline. Participants who were anti-tTG-IgA/IgG+ and HLA-DQ2+ and/or HLA-DQ8+ underwent small bowel biopsy. Results: A total of 8794 children were enrolled, of whom 479 had chronic unexplained abdominal symptoms. Three (0.034%) children were anti-tTG-IgA+ and ten (0.114%) had serum total IgA <0.05 g/L, all of whom were anti-tTG-IgG−. The three positive children were all HLA-DQ2+ and/or HLA-DQ8+. Two underwent gastroscopy, and histopathology of small intestinal biopsy showed duodenal villous blunting in one and increased intraepithelial lymphocytes in the other, neither consistent with a diagnosis of CD. Conclusion: Our study showed a prevalence of CD autoimmunity of 0.034% and failed to identify any cases of CD, suggesting a low prevalence of CD among children in South China.